Repurposing Napabucasin as an Antimicrobial Agent against Oral Streptococcal Biofilms. (21st November 2020) - Kuang, Xinyi; Yang, Tao; Zhang, Chenzi; Peng, Xian; Ju, Yuan; Li, Chungen; Zhou, Xuedong; Luo, Youfu; Xu, Xin
Abstract : Objectives . Disruption of microbial biofilms is an effective way to control dental caries. Drug resistance and side effects of the existing antimicrobials necessitate the development of novel antibacterial agents. The current study was aimed at investigating the antibacterial activities of the repurposed natural compound napabucasin against oral streptococci. Methods . The minimum inhibitory concentration, minimum bactericidal concentration, minimum biofilm inhibition concentration, and minimum biofilm reduction concentration of Streptococcus mutans, Streptococcus gordonii, and Streptococcus sanguinis were examined by a microdilution method. Cytotoxicity of napabucasin against human oral keratinocytes, human gingival epithelia, and macrophage RAW264.7 was evaluated by CCK8 assays. The dead/live bacterium and exopolysaccharide in the napabucasin-treated multispecies biofilms were evaluated by confocal laser scanning microscopy. Microbial composition within the napabucasin-treated biofilms was further visualized by fluorescent in situ hybridization and qPCR. And the cariogenicity of napabucasin-treated biofilms was evaluated by transverse microradiography. Results. Napabucasin exhibited good antimicrobial activity against oral streptococcal planktonic cultures and biofilms but with lessened cytotoxicity as compared to chlorhexidine. Napabucasin reduced the cariogenic S. mutans and increased the proportion of the commensal S. gordonii in the multispecies biofilms. More importantly, napabucasin significantly reduced the demineralization capability of biofilms on tooth enamels. Conclusion . Napabucasin shows lessened cytotoxicity and comparable antimicrobial effects to chlorhexidine. Repurposing napabucasin may represent a promising adjuvant for the management of dental caries.